Assessing motor competence in kicking in individuals with Down syndrome through wearable motion sensors. Issue 6 (26th January 2022) - Quinzi, F.; Camomilla, V.; Sbriccoli, P.; Piacentini, M. F.; Vannozzi, G.
Abstract: Background: Kicking a ball is a very frequent action in sport and leisure time activities and a low proficiency in this skill could limit the participation in recreational sport activities. This issue is emphasised in individuals with Down syndrome (IDS) for which data about motor competence in kicking are limited to children. Here, we aim at evaluating the kicking competence of IDS combining a qualitative and a quantitative method. Methods: Twenty‐three adult IDS and 21 typically developed individuals (ITD) volunteered to participate in the study. Peak‐to‐peak 3D linear acceleration and angular velocity were recorded at 200 samples/s using two inertial measurement units placed on the lower back and lateral malleolus of the dominant limb during kicking. Motor competence in kicking was assessed according to the criteria proposed in the test of gross motor development version 3 (TGMD‐3). Results: Individuals with Down syndrome showed lower motor competence (ITD: 5.9 ± 1.2; IDS: 3.2 ± 2.0) and lower angular velocities about the cranio‐caudal (ITD: 3.0 ± 1.8; IDS: 2.1 ± 1.1 rad/s) and medio‐lateral axes (ITD: 4.5 ± 1.5; IDS: 3.0 ± 1.1 rad/s) of the trunk compared with ITD. Shank angular velocity about the medio‐lateral axis was lower in IDS (ITD: 14.3.6 ± 4.0; IDS: 9.9 ± 2.8 rad/s). Conclusions: The lower trunk angular velocity in IDS may limit the possibility to rely on the proximal‐to‐distal sequencing commonly observed in kicking and generate high shank angular velocity upon ball impact. The lower trunk angular velocity may result from orthopaedic features of the pelvic girdle and possibly from a poorer neuromuscular control of core muscles.